Monte Carlo-based 3-dimensional dosimetry of salivary glands in radioiodine treatment of differentiated thyroid cancer estimated using (124)I PET - HOBBS, R. F (2013)
AIM: Salivary gland toxicity is of concern in radioiodine treatment of thyroid cancer. Toxicity is often observed while the estimated radiation absorbed dose (AD) values are below expected toxicity thresholds. Monte Carlo-based voxelized 3-dimensional radiobiological dosimetry (3D-RD) calculations of the salivary glands from eight metastatic thyroid cancer patients treated with (131)I are presented with the objective of resolving this discrepancy. METHODS: GEANT4 Monte Carlo simulations were performed for (131)I, based on pretherapeutic (124)I PET/CT imaging corrected for partial volume effect, and the results scaled to the therapeutic administered activities. For patients with external regions of high uptake proximal to the salivary glands, such as thyroid remnants or lymph node metastases, separate simulations were run to quantify the AD contributions from both (A) the salivary glands themselves, and (B) the external proximal region of high uptake (present for five patients). The contribution from the whole body outside the field of view was also estimated using modeling. Voxelized and average ADs and biological effective doses (BEDs) were calculated. RESULTS: The estimated average therapeutic ADs were 2.26 Gy considering all contributions and 1.94 Gy from the self-dose component only. The average contribution from the external region of high uptake was 0.54 Gy. This difference was more pronounced for the submandibular glands (2.64 versus 2.10 Gy) compared to the parotid glands (1.88 Gy versus 1.78 Gy). The BED values were on average only 6.6 % higher than (2.41 Gy) the ADs. CONCLUSION: The external sources of activity contribute significantly to the salivary gland AD, however neither this contribution, nor the radiobiological effect quantified by the BED are in themselves sufficient to explain the clinically observed toxicity.